2018
DOI: 10.1097/fjc.0000000000000575
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Anticoagulant Therapy With Cognitive Impairment Among Patients With Atrial Fibrillation: A Meta‐Analysis and Systematic Review

Abstract: OACs significantly reduce the occurrence of cognitive impairment in patients with AF. Compared with warfarin, new oral anticoagulants have an efficiently protective effect on cognition. In the range of INR 2-3, with the increase of TTR, the incidence of cognitive impairment is lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 27 publications
2
53
0
1
Order By: Relevance
“…The findings from this study are in line with a recent meta-analysis (Cheng et al, 2018), which was based on five studies and suggested there was an association between anticoagulant use and reduced incidence of dementia. However, the limitations of previous meta-analysis were the results relied on cross sectional studies, which may introduce bias and confounding, and the effects of VKA alone versus no treatment on dementia were not examined.…”
Section: Discussionsupporting
confidence: 91%
“…The findings from this study are in line with a recent meta-analysis (Cheng et al, 2018), which was based on five studies and suggested there was an association between anticoagulant use and reduced incidence of dementia. However, the limitations of previous meta-analysis were the results relied on cross sectional studies, which may introduce bias and confounding, and the effects of VKA alone versus no treatment on dementia were not examined.…”
Section: Discussionsupporting
confidence: 91%
“…The evidence supporting a direct connection between AF and dementia suggests the possibility that anticoagulant therapy for AF may reduce the incidence of dementia in this population, and results obtained in a number of recent population-based studies suggest that this is indeed the case (Ding et al, 2018;Field et al, 2019;Mongkhon et al, 2019;Silva et al, 2019). Interestingly, while some groups have found that all anticoagulants provide a level of protection (Friberg and Rosenqvist, 2018) most studies report that the direct oral anticoagulants (DOACs) that target thrombin are particularly efficacious (Jacobs et al, 2016;Chen et al, 2018;Cheng et al, 2018). It is tempting to conclude that DOACs reduce the risk of AF-related dementia by decreasing the incidence of thrombotic and/or embolic events, but this scenario may be overly simplistic.…”
Section: Inhibiting Thrombin: Implications For Therapeutic Interventimentioning
confidence: 99%
“…Despite the role of oral anticoagulants as first-line medication in the prevention of ischemic stroke in patients with AF [ 39 ], it is still debatable whether the risk of AF-related dementia can be significantly reduced by oral anticoagulation treatment [ 40 , 41 ]. Recent data suggest that the novel anticoagulants would be a better choice for the prevention of dementia than warfarin (a vitamin K antagonist) [ 42 , 43 ], probably due to a lower rate of intracerebral bleeding [ 43 ]. Secondly, in terms of rhythm control strategies, cardioversion or AF ablation may result in sinus rhythm and improve cardiac output and cerebral perfusion.…”
Section: Psychosocial Consequences Of Afmentioning
confidence: 99%